Closed-loop versus open-loop “remind-to-move” treatment using wearables for hemiparetic upper extremity in patients after stroke: A proof-of-concept study - Kenneth N. K. Fong; Jasmine P. Y. Pak; Alissa H. L. Koo; Maggie M. K. Szeto; Natalie M. T. Wong; Keily K. Y. Yau; Sharon F. M. Toh; Vivian W. Lou; Hector W. H. Tsang; Gary K. K. Lau (Wearable Technologies)
This is a proof-of-concept study to compare the effects of a 2-week program of “Remind-to-move” (RTM) treatment using closed-loop and open-loop wearables for hemiparetic upper extremity in patients with chronic stroke in the community. The RTM open-loop wearable device has been proven in our previous studies to be useful to address the learned nonuse phenomenon of the hemiparetic upper extremity. A closed-loop RTM wearable device, which emits reminding cues according to actual arm use, was developed in this study. A convenience sample of 16 participants with chronic unilateral stroke recruited in the community was engaged in repetitive upper extremity task-specific practice for 2 weeks while wearing either a closed-loop or an open-loop ambulatory RTM wearable device on their affected hand for 3 hrs a day. Evaluations were conducted at pre-/post-intervention and follow-up after 4 weeks using upper extremity motor performance behavioral measures, actual arm use questionnaire, and the kinematic data obtained from the device. Results showed that both open-loop and closed-loop training groups achieved significant gains in all measures at posttest and follow-up evaluations. The closed-loop group showed a more significant improvement in movement frequency, hand functions, and actual arm use than did the open-loop group. Our findings supported the use of closed-loop wearables, which showed greater effects in terms of promoting the hand use of the hemiparetic upper extremity than open-loop wearables among patients with chronic stroke.